Analisis Kinerja Keuangan Emiten Sebelum dan Sesudah Masuk Bursa : Studi Kasus Pada PT X - Purba, Jan Horas Veriyadi (Jurnal Ilmiah Ranggagading (JIR), 2006)
This research was conducted on financial performance analysis of PT X. The amalysis was done toward emiten of the firms that carried out public offering in 2001. The scope of research include growth trend profitability, liquidity position, solvability, activity, and performance in stock exchange. The techniques to analyze data were ratio analysis technique (growth ratio, profitability ratio, liquidity ratio, solvability ratio, activity ratio and market value ratio), common size vertical analysis and trend analysis. The outcome of the research indicates that PT X does not experience escalation in its financial performance. This matter is influenced by three factors, namely (1) venture loss and net loss, (2) debt increase of PT X and (3) per stock bet loss. Keywords: Financial Performance Analysis.